2008
DOI: 10.1111/j.1540-8159.2008.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effect of Cardiac Pacing Mode on Endothelial Vasodilation: Prospective, Double‐Blind, Cross‐Over, Comparative Clinical Study

Abstract: Acute ventricular demand pacing (VVI pacing) is clearly associated with attenuation of FMD in patients with atrial-based pacing systems. The attenuation of endothelial vasodilation might have a role in hemodynamic and clinical deterioration in patients with VVI pacemakers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…An increased LA pressure is associated with arrhythmogenic remodeling (16) and mechano-electric feedback (22), which may promote recurrence of AF. In addition, as mentioned above, right ventricular pacing has recently been demonstrated to cause endothelial dysfunction (17). Endothelial dysfunction is an important predictor of recurrence of AF after catheter ablation (23).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An increased LA pressure is associated with arrhythmogenic remodeling (16) and mechano-electric feedback (22), which may promote recurrence of AF. In addition, as mentioned above, right ventricular pacing has recently been demonstrated to cause endothelial dysfunction (17). Endothelial dysfunction is an important predictor of recurrence of AF after catheter ablation (23).…”
Section: Discussionmentioning
confidence: 97%
“…These factors result in a decreased LV systolic function, mitral regurgitation and higher LA pressure (15), which may promote arrhythmogenic remodeling (16) and increase the incidence of AF. Furthermore, right ventricular pacing has recently been demonstrated to cause systemic endothelial dysfunction, suggesting a novel mechanism for its association with AF (17). A previous study (18) and a metaanalysis (10) reported that atrial pacing also increases the incidence of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Second, right ventricular pacing has recently been demonstrated to cause endothelial dysfunction. 28) Endothelial dysfunction is an important predictor of recurrence of AF after catheter ablation. 23) Third, RV lead induced TR.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 It should be noted, however, that the impact of pacing on endothelial function has been investigated both in terms of atrial-based vs. ventricular demand pacing and in the setting of biventricular pacing in patients with heart failure. Fak et al 38 showed an acute attenuation of flow mediated dilatation in 12 individuals when their pacemakers were programmed to ventricular demand pacing, as opposed to atrial-based pacing and Rubaj et al 20 demonstrated that biventricular pacing, which avoids ventricular dyssynchrony, was associated with reduced oxidative stress, NO metabolites and immune activation, and improved tissue perfusion, compared with right ventricular pacing in heart failure patients. More recently, Akar et al 39 reported that in patients with heart failure and electrical dyssynchrony as evidenced by QRS duration .120 ms, a positive response to cardiac resynchronization therapy (CRT) was more likely in patients with endothelial dysfunction before CRT.…”
Section: Discussionmentioning
confidence: 99%